190k views
3 votes
ES URGENTE me ayudan?

ES URGENTE me ayudan?-example-1

1 Answer

0 votes

Answer:


((3^(-1)+2^(-1))/(5^(-1)))^(-1)+3=(81)/(25)

Explanation:

Given expression is,


((3^(-1)+2^(-1))/(5^(-1)))^(-1)+3

By solving the given expression,


((3^(-1)+2^(-1))/(5^(-1)))^(-1)+3=(((1)/(3)+(1)/(2))/((1)/(5)))^(-1)+3


=(((2+3)/(6))/((1)/(5)))^(-1)+3


=(((5)/(6))/((1)/(5)))^(-1)+3


=((5)/(6)* (5)/(1))^(-1)+3


=((25)/(6))^(-1)+3


=(6)/(25)+3


=(6+(25* 3))/(25)


=(81)/(25)

User Samiullah Khan
by
6.0k points